1996 IEEE MTT-S International Microwave Symposium Digest
DOI: 10.1109/mwsym.1996.511075
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of broadband, high efficiency feedforward amplifiers

Abstract: a Ϫ3-dBm input level. Figure 3 shows the resultant improvement in the 3 rd -order intermodulation products for the linearized and unlinearized cases.For such a case where the circuit has been optimized for 10 GHz, in addition to the significant improvement in 3 rd -order intermodulation at the optimization frequency, the result also shows improvement over at least the 2-14-GHz range. The complex combination of the amplitude and phase balance in the first and second loops determines this bandwidth.The rapid det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The estimated return loss was −31.82 dB, derived from (8), at a center frequency of 2.14 GHz. Then, the LE circuit was converted into the TLR using (9). The calculated characteristic impedance for the QS was 60.16 Ω, as shown in Fig.…”
Section: Circuit Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated return loss was −31.82 dB, derived from (8), at a center frequency of 2.14 GHz. Then, the LE circuit was converted into the TLR using (9). The calculated characteristic impedance for the QS was 60.16 Ω, as shown in Fig.…”
Section: Circuit Implementationmentioning
confidence: 99%
“…The feedforward linearization is well known for its broad bandwidth capability, good linearization performance, and its stable operation. However, poor system efficiency is the critical disadvantage of the feedforward amplifier [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Non-linearities in wireless-based ultra-wideband communications are responsible for a phenomena that degrades system's performance and must be minimized [1]. One solution to this problem is broadband linearization.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of new methods have been proposed, feedforward remains one of the most popular technologies, due to its providing the highest amount of distortion cancellation [3][4][5][6][7][8][9]. Hence, many previous works involving its implementation and analysis have been published, in order to analyze or improve the feedforward system [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many previous works involving its implementation and analysis have been published, in order to analyze or improve the feedforward system [3][4][5][6][7][8][9]. Yang et al [9] reported a method of optimizing the 2 nd -loop parameters of a feedforward system using a simple mathematical model.…”
Section: Introductionmentioning
confidence: 99%